Trend in the Literature Review of Entrepreneurial Orientation: A Bibliometric Analysis - Nuryakin (Studies in Business and Economics)
This article reviewed the literature on entrepreneurial orientation with a bibliometric analysis approach to measure how this concept has developed over the last decade in the business and management domains, identify research trends, and propose a plan for future studies. The merging bibliography through data was extracted from the Scopus Database using the bibliometric method of 2,349 documents and was then filtered into 260 research articles from 2011 – 2021. Bibliometric techniques were conducted using citation, co-citation analysis and co-occurrence of author keywords. This research revealed the nature and direction of research that the entrepreneurial orientation field has taken in the last decade. Nine clusters stood out as important issues in the research on entrepreneurial inclination. The most influential publications, writers, nations, and institutions were also identified by this survey related to research on entrepreneurial orientation with possible future research directions in entrepreneurial orientation. This research is limited to only using a single database sourced from the Scopus indexer without adding databases from other indexers and only explains its inability to contextualize the citation structure of the articles.